New York, Leo Baeck Institute, Archives - Leo Baeck Institute (2009)
[Dt.:] Das Archiv des Leo Baeck Institutes in New York dokumentiert die deutsch-jüdische Geschichte in Deutschland. Das Archiv benannt nach dem Rabbiner Leo Baeck (1873-1956) bewahrt zahlreiche Nachlässe namhafter deutscher Juden und verwaltet das Werk jüdischer Künstler, darunter Architekten, Bildhauer, Illustratoren, Satiriker etc. Ein Online-Katalog ermöglicht die Recherche des Bestandes. - [Engl.:] The Archive of the Leo Baeck Institute in New York documents the German-Jewish history in Germany. The archive is named after Rabbi Leo Baeck (1873-1956) and holds the bequests of prominent German Jews and records the works of Jewish artists, architects, sculptors, satirists, etc. The archive collection can be searched through an online-catalogue.